2016
DOI: 10.1177/0265407516662920
|View full text |Cite
|
Sign up to set email alerts
|

How do emerging adults respond to exercise advice from parents? A test of advice response theory

Abstract: Advice response theory (ART) proposes advisor characteristics, advice politeness, and advice content impact recipient perceptions of advice quality, their intention to implement the advice, and their coping. However, ART has primarily been examined in friend-to-friend advising on academic, romantic, or social issues. To test ART in an understudied relational and topical context, emerging adults ( N = 196, aged 18–28 years) were surveyed about physical activity or exercise advice they received from a parent. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
(154 reference statements)
2
21
1
Order By: Relevance
“…Second, our findings add to studies suggesting a complex relationship between positive feasibility and advice outcomes (e.g., Feng & MacGeorge, 2010). In contrast with past findings showing positive (Feng & MacGeorge, 2010) and negative (Guntzviller et al, 2017) effects of feasibility perceptions on advice outcomes, we observed an interaction between positive feasibility and instruction. Further work is needed to determine how advisors’ talk about the feasibility of an advised action is associated both with recipients’ perception of that feasibility and their responses to the advice in different relationships and contexts.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Second, our findings add to studies suggesting a complex relationship between positive feasibility and advice outcomes (e.g., Feng & MacGeorge, 2010). In contrast with past findings showing positive (Feng & MacGeorge, 2010) and negative (Guntzviller et al, 2017) effects of feasibility perceptions on advice outcomes, we observed an interaction between positive feasibility and instruction. Further work is needed to determine how advisors’ talk about the feasibility of an advised action is associated both with recipients’ perception of that feasibility and their responses to the advice in different relationships and contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…However, when instruction levels were lower, there was a negative association between positive feasibility talk and patient satisfaction (Figure 1C). In the absence of instruction, an overemphasis on the feasibility of a recommendation may be perceived as threatening to autonomy and patronizing, and, therefore, induce reactance (Guntzviller et al, 2017). This finding is consistent with past work indicating that emerging adults become irritated when health advice from their parents emphasizes the feasibility of the recommended behaviors (Guntzviller et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Hispanic community, it is customary for parents to provide lengthy and emotionally charged consejos , or parental advice lectures, to display concern for and engagement with their children (Alfaro, O’Reilly-Díaz, & Lopez, 2014; Holloway et al, 2014). Advisors may intend for advice to be supportive, informational, and/or influential (MacGeorge, Feng, & Guntzviller, 2016), but advice recipients can perceive advice, specifically advice about exercise, as overstepping, hurtful, and relationally damaging (Burke & Segrin, 2014; Guntzviller, Ratcliff, Dorsch, & Osai, 2017). Advice response theory (ART) predicts how the advice recipient’s perceptions of the advisor and advice message features drive the recipient’s emotional response and willingness to follow the advised action (B.…”
mentioning
confidence: 99%